2017
DOI: 10.1177/0739986316688877
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Early Literacy With Hispanic Preschoolers: The Factor Structure of the Phonological Awareness Literacy Screening—Español

Abstract: For two decades, it has been recommended that assessment of literacy for preschool children be conducted in a child's primary language. However, only a few literacy assessments have been validated with a preschool, Spanish-speaking population. The purpose of the present study was to test the latent structure of the Phonological Awareness Literacy Screening for Preschool (PALS-PreK) Español with a sample of Spanish-speaking children in the southwestern United States. Children who could recognize at least 16 upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…The LS task loaded on both factors. Yaden, Marx, Cimetta, Alkhadim, and Cutshaw (2017) replicated the work of Townsend and Konold using a short, draft version of PALS español PreK. They too found that the same two correlated factors fit better than a single-factor model.…”
Section: Factor Structure Of Pals Assessmentssupporting
confidence: 64%
See 3 more Smart Citations
“…The LS task loaded on both factors. Yaden, Marx, Cimetta, Alkhadim, and Cutshaw (2017) replicated the work of Townsend and Konold using a short, draft version of PALS español PreK. They too found that the same two correlated factors fit better than a single-factor model.…”
Section: Factor Structure Of Pals Assessmentssupporting
confidence: 64%
“…Nevertheless, his work championed the bifactor model, and it is consistent with our results. Considering that Yaden et al (2017) found support for a model with two correlated factors when using task-level item parcels but we did not when conducting an item-level analysis, the analytic procedure may be affecting the results. It is difficult to know for sure as Yaden et al used a shorter, preliminary version of the measure.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations